Characterization and epitope mapping of a panel of monoclonal antibodies against HIV‐1 matrix protein. (25th April 2018) - Zhang, Zhiqing; Zhang, Feng; Bai, Shimeng; Qiao, Jiaming; Shen, Honglin; Huang, Fang; Gao, Shuangquan; Li, Shaowei; Gu, Ying; Xia, Ningshao
Abstract: The HIV‐1 Gag precursor protein (p55) is the main structural protein comprising the matrix (MA/p17), capsid (CA/p24), and nucleocapsid (NC/p7) proteins, and is uniquely responsible for virion assembly within the virus life cycle. The MA protein plays a critical role in plasma membrane targeting and envelope glycoprotein (Env) uptake during virion assembly. Yet, when viral infection occurs, the MA protein may also be involved in virion uncoating, dissociating from the plasma membrane, and participating in the nuclear importation process. Thus, the MA protein contains a reversibly membrane‐binding signal and varied conformation to govern its subcellular localization and biological functions. However, these purported different conformations of the MA protein during assembly are poorly understood, especially in terms of its function as a component of the precursor protein. In this study, we characterized a panel of monoclonal antibodies against MA that showed discrete reactivity to p55, an intermediate (p41), and the final p17 mature form. We suggest that these antibodies could be used to track the different conformations of MA during the HIV‐1 life cycle, particularly during HIV‐1 assembly and maturation, and contribute to structure determination of MA or MA precursors. These antibodies would also have clinical value, including serving for therapeutic strategy to interfere AIDS progression, reagent in diagnostic kit for the detection of virion‐free p17 or p17 derived from virion lysate.